Critical Thinking Questions in the Reading Section of EFL Textbooks - Sri Yuliana; Novalita Fransisca Tungka (Universitas Brawijaya, 2018)
In this article, we discuss how far EFL textbooks used as teaching materials for second grade students in senior high schools in Poso regency, Central Sulawesi province, accommodate critical thinking skill in the textbook’s reading comprehension section. The assumption underlying this discussion is that an ideal EFL textbook is supposed to meet the needs to accommodate critical thinking skill as one of the required skills in the 21st century. In doing so, Revised Bloom’s Taxonomy and four levels of comprehension were used to examine the questions level and which level of reading comprehension each question falls into. The sources of data were two commercially published and one government-published EFL textbooks. The discussion in this paper leads to which EFL textbook accommodates critical thinking skill in the form of WH questions in its reading comprehension section.